2017
DOI: 10.1590/1981-863720170001000033062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of restoration technique on stress distribution in extensively destroyed premolars: a finite element analysis study

Abstract: Objective Results Under the axial load, a higher concentration of stresses was observed around the cast post (166 MPa). In the oblique load simulation, there was a concentration of stresses on the buccal root wall, internally and externally, in the tooth restored with cast post (222 MPa). In both load directions, the glass fiber post dissipated the stress received with greater uniformity (55 to 111 MPa). ConclusionThese data suggested that from the biomechanical point of view, the use of a glass fiber post and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…is resulted from similarity of post systems and materials used as previously stated. Moreover, using resin cement, resin composite, core build-up material, and posts with comparable modulus of elasticity to dentin created mechanically homogeneous restoration as reported in previous studies [16,29].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…is resulted from similarity of post systems and materials used as previously stated. Moreover, using resin cement, resin composite, core build-up material, and posts with comparable modulus of elasticity to dentin created mechanically homogeneous restoration as reported in previous studies [16,29].…”
Section: Discussionsupporting
confidence: 70%
“…The better stress distribution pattern and reparable failure mode of fiber post were also supported by various studies [ 5 , 19 ]. Likewise, a finite element analysis study showed that fiber post displayed better uniformity in stress distribution compared to stiffer material such as gold cast post [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, GFP has an elastic modulus of 30 to 50 GPa 5,21) . GFPs have longitudinal fibers joined uniformly by composites, thus transferring less stress to the restorative material, and providing high flexural and fatigue strength, and high stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional models for finite element analysis were created based on a computed tomography image (i-CAT Cone Beam 3D Dental Imaging System; Imaging Sciences International, Norcros, GA, USA) reproducing the maxillary central incisor (21). The images obtained from the CT scan were used as a basis for the computational construction of the anterior maxillary region (25.0 mm in height×15.0 mm in mesiodistal width×15.0 mm in bucco-palatal depth) constructed from type 3 bone tissue (thin layer of cortical bone -1.0 mmaround a trabecular bone), according to its density.…”
Section: Methodsmentioning
confidence: 99%